2019
DOI: 10.1016/j.celrep.2019.07.106
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection and Analysis of Neoantigen-Specific T Cell Populations from Tumors and Blood

Abstract: SUMMARYNeoantigen-specific T cells are increasingly viewed as important immunotherapy effectors, but physically isolating these rare cell populations is challenging. Here, we describe a sensitive method for the enumeration and isolation of neoantigen-specific CD8+ T cells from small samples of patient tumor or blood. The method relies on magnetic nanoparticles that present neoantigen-loaded major histocompatibility complex (MHC) tetramers at high avidity by barcoded DNA linkers. The magnetic particles provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 57 publications
(80 reference statements)
0
53
0
Order By: Relevance
“…These molecules are new to the immune system and may trigger an immune response. It has been reported that in patients with melanoma, a personalized treatment vaccine generated a robust immune response against the cancer and may have helped to prevent it from returning [66]. Although this clinical trial is in the I phase, the studies confirm the potential of neo-antigen vaccines to treat cancer and should lead to larger trials in the future in order to help address such challenges for effective cancer immunotherapy.…”
Section: Vaccinementioning
confidence: 73%
“…These molecules are new to the immune system and may trigger an immune response. It has been reported that in patients with melanoma, a personalized treatment vaccine generated a robust immune response against the cancer and may have helped to prevent it from returning [66]. Although this clinical trial is in the I phase, the studies confirm the potential of neo-antigen vaccines to treat cancer and should lead to larger trials in the future in order to help address such challenges for effective cancer immunotherapy.…”
Section: Vaccinementioning
confidence: 73%
“…Of note, all mutated TSAs detected using these methods are restricted to individual tumours. Shared mutated TSAs that can be detected in more than one patient are currently elusive 58,59 . The reasons why TSAs seem to be so difficult to detect have yet to be completely elucidated but might reflect technical limitations of the employed detection and/or discovery methodologies (TAbLe 2), as well as immunoediting by the patient's initial antitumour immune response, leading to elimination of the most antigenic tumour clones.…”
Section: Alternative Sequence Antigensmentioning
confidence: 99%
“…Furthermore, T cell recognition of TSAs might lead to the upregulation of inhibitory ligands, such as PD-L1, and contribute to the development of an immunosuppressive tumour microenvironment, both of which might impede the expansion and response of antigen-specific T cells 60,61 . In summary, antigen-specific T cells against a specific mutated TSA can frequently be detected in the absence of a robust antitumour immune response 35,49,50,59,62 , and thus the antigen either must have previously been present, but has been removed by immunoediting 59 , or still prevails but remains undetectable by MS/MS. Exonic variants potentially leading to mutated TSAs (fIg.…”
Section: Alternative Sequence Antigensmentioning
confidence: 99%
“…As a result, up to thousands of unique specificities can be potentially identified simultaneously, paving the way for high-throughput platforms and downstream applications such as TCR redirected T-cell therapy ( 60 , 61 ). Of note, state-of-the-art microfluidic devices can help with potential sample size limitation by allowing on-chip detection and manipulation of multimer-sorted neoantigen-specific T cells for downstream analysis and applications ( 38 ).…”
Section: Current Toolset For the Enrichment Of Predefined Neoantigen mentioning
confidence: 99%
“…In this regard, Cohen et al ( 22 ) first provided a simplified and noninvasive blood-based strategy as an alternative to current TIL production by demonstrating that neoantigen and self-antigen reactive T-cells can be reliably isolated from the peripheral blood of melanoma patients. Detection of neoantigen-specific CD8 + and CD4 + lymphocytes from peripheral blood has been subsequently described in patients with relatively low tumor mutation burden, such as ovarian and gastrointesinal cancers ( 20 , 38 40 ). However, circulating neoantigen-specific T-cells share with their infiltrating counterpart very low detection frequencies (ranging from 0.5 to 0.002%) ( 20 , 22 , 37 , 41 , 42 ), hence the need for specific enrichment strategies.…”
Section: Introductionmentioning
confidence: 99%